3, 5‐Diiodothyronine protects against cardiac ischaemia–reperfusion injury in male rats. Issue 11 (21st October 2021) - Louzada, Ruy Andrade; Padron, Alvaro Souto; Marques‐Neto, Silvio Rodrigues; Maciel, Leonardo; Werneck‐de‐Castro, João Pedro; Ferreira, Andrea Claudia Freitas; Nascimento, Jose Hamilton Matheus; Carvalho, Denise Pires
Abstract : New Findings: What is the central question of this study? 3, 5‐Diiodothyronine (3, 5‐T2) administration increases resting metabolic rate, prevents or treats liver steatosis in rodent models, and ameliorates insulin resistance: what are its effects on cardiac electrical and contractile properties and autonomic regulation? What is the main finding and its importance? Chronic 3, 5‐T2 administration has no adverse effects on cardiac function. Remarkably, 3, 5‐T2 improves the autonomous control of the rat heart and protects against ischaemia–reperfusion injury. Abstract: The use of 3, 5, 3′‐triiodothyronine (T3) and thyroxine (T4) to treat metabolic diseases has been hindered by potential adverse effects on liver, lipid metabolism and cardiac electrical properties. It is recognized that 3, 5‐diiodothyronine (3, 5‐T2) administration increases resting metabolic rate, prevents or treats liver steatosis in rodent models and ameliorates insulin resistance, suggesting 3, 5‐T2 as a potential therapeutic tool. However, a comprehensive assessment of cardiac electrical and contractile properties has not been made so far. Three‐month‐old Wistar rats were daily administered vehicle, 3, 5‐T2 or 3, 5‐T2+T4 and no signs of atrial or ventricular arrhythmia were detected in non‐anaesthetized rats during 90 days. Cardiac function was preserved as heart rate, left ventricle diameter and shortening fraction in 3, 5‐T2‐treated rats compared to vehicle and 3, 5‐T2+T4 groups. Power spectral analysis indicated an amelioration of the heart rate variability only in 3, 5‐T2‐treated rats. An increased baroreflex sensitivity at rest was observed in both 3, 5‐T2‐treated groups. Finally, 3, 5‐T2 Langendorff‐perfused hearts presented a significant recovery of left ventricular function and remarkably smaller infarction area after ischaemia–reperfusion injury. In conclusion, chronic 3, 5‐T2 administration ameliorates tonic cardiac autonomic control and confers cardioprotection against ischaemia–reperfusion injury in healthy male rats.